Disappearing and endangered butterfly species Ropalocera (Papilionoidea + Hesperioidea) of the central part of Poland - Skalski, Andrzej W. (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
Based on own research and data from literature, the author created a list of endangered and extinct butterfly species in central part of Poland. He also brought forward the direction of change. He has also prepared proposals and notions for investors of country adm inistration in the field of managing of National Parks and all other landholders.